Production from macro algae as a biofuel for diesel engine - Rahim A.F.; Sulaiman O.O.; Ahmed A.N. (Research India Publications, 2023)
Plant oils or triglycerides are converted through the trans-esterification reaction with methanol and base catalyst to produce fatty acid methyl esters (FAME) or Biodiesel. Production of biodiesel from plant oil is a renewable, sustainable and alternative of petroleum based fuel. Algae oil (AO) from macroalgae has the potential to become a sustainable fuel source as biodiesel. The lipid contents or oil in algae, once extracted and purified, represent an excellent sustainable feedstock for biodiesel production. Ulva Lactucaspecies of macroalgae were used for algal oil extraction in this study. The AO was extracted by chemical extraction method. The transesterification reaction of AO with methanol and base catalyst was used for the production of biodiesel. In engine performance test, it showed slight increase in specific fuel consumption but biodiesel blends showed higher brake power. The emission of CO, HC and NOx reduced as biodiesel blend percentage increased over engine speed range. Research India Publications.